Tumor Mutation Burden Predicts Relapse in Papillary Thyroid Carcinoma With Changes in Genes and Immune Microenvironment - Guo, Mengli; Chen, Zhen; Li, Yayi; Li, Sijin; Shen, Fei; Gan, Xiaoxiong; Feng, Jianhua; Cai, Wensong; Liu, Qingzhi; Xu, Bo (Frontiers in Endocrinology, 2021)
Background: The risk factors of papillary thyroid carcinoma (PTC) recurrence are meaningful for patients and clinicians. Tumor mutational burden (TMB) has been a biomarker for the effectiveness of immune checkpoint inhibitor (ICI) and prognosis in cancer. However, the role of TMB and its latent significance with immune cell infiltration in PTC is still unclear. Herein, we aimed to explore the effect of TMB on PTC prognosis. Material and Methods: RNA-seq and DNA-seq datasets of PTC patients were downloaded from The Cancer Genome Atlas (TCGA) database. The Gene Ontology (GO) and gene set enrichment analysis (GSEA 4.0.1) were applied further to explore potential differences in PTC patients' biological functions. The differentially expressed genes (DEGs) and immune microenvironment between the high and low TMB groups were determined. Results: TMB had the highest AUC score than other clinical indicators in ROC analysis on recurrence-free survival, and a higher TMB score was related to a worse prognosis. Further, GSEA showed a higher level of oxidative phosphorylation (OXPHOS) in the high TMB group, and 4 genes correlated with recurrence-free survival rate were identified. The abundance of CD8+ T cells and M1 macrophages in the high TMB group was significantly lower than those in the low TMB group. Conclusions: Our study found that TMB was a better predictor variable at evaluating the risk of PTC recurrence. Moreover, TMB-related genes conferred dramatically correlated prognosis, which was worth exploring in guiding postoperative follow-up and predicting recurrence for PTC patients.